Pemberdayaan Kelompok Wanita Tani (KWT) di Kelurahan Kahuripan - Rusli, Damay; Permadi, Cicip Zemi; Haryono, Dandan (CV. Publikasi Indonesia, 2022)
The empowerment of the Women Farmers Group has not been achieved properly as a result of the implementation of empowerment measures that have not been fully implemented by the Kahuripan Village Head and the Agricultural Extension Agency (BPP) of Kahuripan Village, Tawang District, Tasikmalaya City. The purpose of this study was to determine the empowerment of the Women Farmers Group (KWT) in Kahuripan Village, Tawang District, Tasikmalaya City. The method used in this study is a qualitative descriptive research method as a